Identifikasi Failure mode Pada Pekerjaan Struktur Bangunan Gedung SDN Kalibata Kota Palangka Raya - Manurung, Jeremia; Kristiana, Wita (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2026)
Structural work on multi-storey buildings, such as foundations, sloofs, columns, beams, and floor slabs, carries a high level of technical risk and has the potential to cause failure in aspects of OHS, quality, technical, cost, and time. However, previous studies generally only focus on one risk dimension without classifying risks multidimensionally and do not describe the risks per structural work item specifically. This study aims to identify potential failure modes in all structural work items of the 2-storey Kalibata Elementary School building construction project in Palangka Raya City. The method used is descriptive qualitative through three stages of identification, namely literature study, field observation, and interviews, which were then validated by two competent respondents from the contractor and the supervising consultant. The results showed that of the 83 potential failure modes identified in 15 structural work items, 74 were deemed relevant and 9 were irrelevant to the actual conditions of the project. The identified failure modes were dominated by the OHS risk category, followed by aspects of quality, technical, and cost and time. This study also found a number of new failure modes that have not been documented in previous literature, which reflect the specific characteristics of educational building projects in Central Kalimantan.